Emotion talk in the context of young people self‐harming: facing the feelings in family therapy. Issue 2 (15th March 2016) - Rogers, Alice; Schmidt, Petra
Abstract : This article describes the use of emotion talk in the context of using a manualised approach to family therapy where the presenting problem is self‐harm. Whilst we understand that there is an internal aspect to emotion, we also consider emotions to be socially purposeful, culturally constructed and interactional. We found that within the presenting families, negative emotions were often talked about as located within the young person. Through using 'emotion talk' (Fredman, 2004 ) in deconstructing and tracking emotions and exploring how emotions connected to family‐of‐origin and cultural contexts, we developed an interactional understanding of these emotions. This led to better emotional regulation within the family and offered alternative ways of relating. The article discusses the use of relational reflexivity, and using the therapist and team's emotions to enable the therapeutic process, encouraging reflexivity on the self of the therapist in relation to work with emotions. Practitioner points: Emotions can be seen as both a reflection of feelings experienced by the individual and as a communication. An interactional understanding of emotions can be used therapeutically. Therapists should explore emotional displays and track the interactional patterns within the therapeutic system. Therapists should self‐reflexive about ways of doing emotions and use this awareness in practice.